Racial differences in the association of accelerated aging with future cardiovascular events and all-cause mortality: the coronary artery risk development in young adults study, 2007–2018. Issue 5 (4th July 2022) - Forrester, Sarah N.; Zmora, Rachel; Schreiner, Pamela J.; Jacobs, David R.; Roger, Veronique L.; Thorpe, Roland J.; Kiefe, Catarina I.
ABSTRACT: Objective: Variability of Cardiovascular disease (CVD) risk, including racial difference, is not fully accounted for by the variability of traditional CVD risk factors. We used a multiple biomarker model as a framework to explore known racial differences in CVD burden. Design: We measured associations between accelerated aging (AccA) measured by a combination of biomarkers, and cardiovascular morbidity and all-cause mortality using data from the Coronary Artery Risk Development in Young Adults study (CARDIA). AccA was defined as the difference between biological age, calculated using biomarkers with the Klemera and Doubal method, and chronological age. Using logistic regression, we assessed overall and race-specific associations between AccA, CVD, and all-cause mortality. Results: Among our cohort of 2959 Black or White middle-aged adults, after adjustment, a one-year increase in AccA was associated with increased odds of CVD (Odds Ratio (OR) = 1.04; 95% CI: 1.02, 1.06), stroke (OR = 1.12; 95% CI: 1.07, 1.17), and all-cause mortality (OR = 1.05; 95% CI: 1.02, 1.08). We did not find significant overall racial differences, but we did find race by sex differences where Black men differed markedly from White men in the strength of association with CVD (OR = 1.06, 95% CI: 1.01, 1.12). Conclusions: We provide evidence that AccA is associated with future CVD.